Study on the allocation of congestion revenue under doubletrack pricing system. Issue 1 (January 2021) - Zhang, Maolin; Xing, Yuhui; Wang, Bangcan; Chen, Qinggui; Liu, Xiangrui; Mu, Chunfeng; Li, Wenxuan
Abstract: The introduction of nodal spot market has brought unneglectable problem of congestion revenue allocation in China. Meanwhile, the coexistence of market and regulation in nowadays power market in China added specialty when it comes to appropriately allocate congestion revenue in China. Based on thorough review and analysis on both the principle of congestion revenue allocation as well as the status quo of a typical provincial market in China, this paper attempts to tackle this problem with consideration on property right, with which the contribution to the grid network of electricity users are taken into account. The solution is established in two stages, which is based on the reality that the distribution of two types of users in each node remains currently unknown.